EXPLORING THE IMPACT OF COVID-19 ON TOURISM INDUSTRY OF BANGLADESH: AN EMPIRICAL STUDY - Bagchi, Sraboni (International Journal of Research -GRANTHAALAYAH, 2021)
The tourism industry is one of the fastest-growing service industries in Bangladesh. This industry observed consistent economic growth for the last five years and contributed significantly to the GDP of Bangladesh. The outbreak of the Covid-19 pandemic impacted the tourism industry notedly. This paper aims to explore the impact on the tourism industry of Bangladesh, considering the economic and environmental aspects. The study found a catastrophic impact on the tourism industry's economic growth, which also affects the country’s total GDP growth. The tourism industry is expected to contribute 1309.27 billion Taka, which would be 3.20% of the total GDP of Bangladesh, but the actual contribution is 539.60 billion Taka which is 1.70% of total GDP. The pandemic also negatively affected employment opportunities, tourists’ arrival rate, hotel occupancy rate, and total tourism expenditures. On the other hand, despite some negative issues, Covid-19 impacted positively on the natural environment. The air quality improved, water pollution, noise pollution, consumption of natural resources, emission of greenhouse gas reduced notably. Considering the positive impacts on the environment, this study also formulated some possible recovery strategies to regain the economic losses through sustainable tourism development.